Book review: Christopher Fleming, Ownership and Inheritance in Sanskrit Jurisprudence. (October 2022) - Wright, Samuel
Christopher Fleming, Ownership and Inheritance in Sanskrit Jurisprudence . New York: Oxford University Press, 2021, 272 pp.